2004
DOI: 10.1007/s00467-003-1373-0
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of urinary cystatin C to urinary creatinine for detecting decreased GFR

Abstract: Glomerular filtration rate (GFR) and urine and serum concentrations of cystatin C and creatinine were measured in 40 boys and 42 girls. The fractional excretion of cystatin C (FE Cyst C) increased in proportion to the decrease in GFR. Since serum creatinine concentration (S-Creatinine) in the numerator of the fractional excretion equation and serum cystatin C concentration (S-Cystatin C) in the denominator have similar numerical values, they cancel out. The result is an equation in which the FE Cyst C is equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…Recently, we found that U-CysC and U-␤2M significantly increase in CKD stages 4 and 5 (17). Furthermore, the ratio of U-Cys to U-Cr has been reported as a reliable screening tool for detecting decreased GFR in pediatric CKD patients (26). However, conflicting results have been reported by a recent study performed in children and adults, which indicated a poor accuracy of U-Cys/U-Cr as an indicator of an eGFR Ͻ60 ml·min Ϫ1 ·1.73 m Ϫ2 (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that U-CysC and U-␤2M significantly increase in CKD stages 4 and 5 (17). Furthermore, the ratio of U-Cys to U-Cr has been reported as a reliable screening tool for detecting decreased GFR in pediatric CKD patients (26). However, conflicting results have been reported by a recent study performed in children and adults, which indicated a poor accuracy of U-Cys/U-Cr as an indicator of an eGFR Ͻ60 ml·min Ϫ1 ·1.73 m Ϫ2 (27).…”
Section: Discussionmentioning
confidence: 99%
“…The urinary cystatin-C (uCysC) concentration can be used as a marker of renal function. 19,20 The ratio of uCysC to urinary creatinine is considered to be a reliable screening tool for detecting decreased GFR in children, 20 and we and other authors have demonstrated that increased uCysC is an independent predictor of AKI during the first days of life in neonates. 21,22 Therefore, the urinary levels of CysC, albumin, and α 1 -microglobulin as well as urinary electrolyte excretion were measured to evaluate neonatal renal glomerular and tubular function in this study.…”
Section: Introductionmentioning
confidence: 91%
“…Nonetheless, the proofs that such rate of urinary excretion of Cys-C reflects the early change of tubular function and GFR if the clearance rate of Cr is normal have been reported. 17,18 After passing through the base membrane of glomeruli, most of the Cys-C are absorbed in the proximal tubule, degraded, and excreted to the urine. According to Tian et al 19 as GFR is decreased, urinary excretion of Cys-C and the FE of Cys-C were increased.…”
Section: Discussionmentioning
confidence: 99%